Islam in Foreign Policy: Promotion of Moderate Islam in Indonesia Foreign Policy 2004-2014 - Andi Purwono (Indonesian Journal of International Relations, 2017)
In Soesilo Bambang Yudhoyono administration, the shift/ dynamics occurred in Indonesia foreign policy. In contrast to the exclusion and rejection of Islam as identity in official statement in Old and New Order, Indonesia actively promote moderate Islam in international relations. Using qualitative method, this document- based research argue that promotion of moderate Islam in Indonesia foreign policy was constructed by Islamic norm, Islam rahmatan lil alamin norm. This norm can be found by tracing the emergence process as mentioned by Finnemore and Sikkink’s Norms Life Cycle Model. The finding suggested some conformity to the model and some deviation especially in term of state actor and their motivation.